2015
DOI: 10.1111/bjh.13475
|View full text |Cite
|
Sign up to set email alerts
|

Reduced doses of cladribine and cytarabine regimen was effective and well tolerated in patients with refractory‐risk multisystem Langerhans cell histiocytosis

Abstract: were re-imaged within the recommended time period had a shorter duration of oral antifungal therapy, emphasizing the importance of minimizing delayed imaging. Further collaborative studies would help to characterize stopping criteria in larger cohorts of patients. AcknowledgementsThis work was undertaken at University College London Hospitals/University College London, which received a proportion of funding from the Department of Health's NIHR Biomedical Research Centres funding Scheme. Author contributionsAll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 11 publications
0
26
0
1
Order By: Relevance
“…Six patients received six courses and three received five due to toxic events. Six patients achieved a complete remission after the planned therapy, and the overall probability of survival at 3 years was estimated to be 73%, with much less toxicity than with the higher dose regimen 48 …”
Section: Treatment Of Lchmentioning
confidence: 95%
See 1 more Smart Citation
“…Six patients received six courses and three received five due to toxic events. Six patients achieved a complete remission after the planned therapy, and the overall probability of survival at 3 years was estimated to be 73%, with much less toxicity than with the higher dose regimen 48 …”
Section: Treatment Of Lchmentioning
confidence: 95%
“…However, this regimen is associated with significant toxicity; treatment‐related death was 8%, and profound myelosuppression resulted in high rates of severe infectious complications 46 . Rosso et al have explored a lower dose regimen; in a series of nine patients with refractory multi‐system LCH with risk‐organ involvement, low‐dose cytarabine (100 mg/m 2 /day for 4 days) was combined with cladribine (5 mg/m 2 /day for 5 days) in monthly cycles 48 . Six patients received six courses and three received five due to toxic events.…”
Section: Treatment Of Lchmentioning
confidence: 99%
“…LCH is characterized by invasive lesions with multiple cell type infiltrations, including pathological CD1a 1 CD207 1 cells affecting one or several organs. [1][2][3][4][5] The etiology of LCH is unknown, and debate centers on LCH resulting from either a malignant transformation of Langerhans cell (LC) precursors or as consequence of a deregulated immune response giving rise to pathological LCs from immature myeloid cells. 2,6,7 LCs are potent antigen-presenting cells of the epidermis that self-renew in the steady state 8 but are recruited in waves after inflammation from the circulation.…”
Section: Introductionmentioning
confidence: 99%
“…A literature review identified only one case report in the United States, 19 one survey of 5 cases without risk organs, 19,20 a small survey from China (written in Chinese), 21 and a retrospective survey of 9 cases in Argentina. 22 An important finding in this study involves the DAS (supplemental Table 3). Due to the varied clinical manifestations of LCH, a comprehensive LCH activity scoring system was used to determine the initial severity of the disease and to objectively assess the efficacy of therapy.…”
mentioning
confidence: 97%